Inlaying Bismuth Nanoparticles on Graphene Nanosheets by Chemical Bond for Ultralong‐Lifespan Aqueous Sodium Storage - Zhu, Haojie; Wang, Fangcheng; Peng, Lu; Qin, Tingting; Kang, Feiyu; Yang, Cheng (Angewandte Chemie International Edition, 2023)
Rechargeable aqueous sodium ion batteries (ASIBs) are rising as an important alternative to lithium ion batteries, owing to their safety and low cost. Metal anodes show a high theoretical capacity and nonselective hydrated ion insertion for ASIBs, yet their large volume expansion and sluggish reaction kinetics resulted in poor electrochemical stability. Herein, we demonstrate an electrode cyclability enhancement mechanism by inlaying bismuth (Bi) nanoparticles on graphene nanosheets through chemical bond, which is achieved by a unique laser induced compounding method. This anchored metal‐graphene heterostructure can effectively mitigate volume variation, and accelerate the kinetic capability as the active Bi can be exposed to the electrolyte. Our method can achieve a reversible capacity of 122 mAh g−1 at a large current density of 4 A g−1 for over 9500 cycles. This finding offers a desirable structural design of other metal anodes for aqueous energy storage systems. Reinforcing bismuth nanoparticles on laser‐induced graphene nanosheets were introduced for an electrically rechargeable aqueous sodium‐ion battery for the first time, which could achieve long‐term operation stability based on a chemical anchoring effect.